The Role of The Joint Audit in Reducing the audit expectations gap - A field study - Babiker, Bashir Bakri Agib (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the role of the joint audit in reducing the expectations gap for auditing, and to clarify the role of the joint audit in identifying the risks surrounding the external audit operations. The study followed both the descriptive analytical method. The study concluded that there is a positive effect between the advantages of joint auditing and reducing the expectations gap in auditing, and the presence of a positive effect between the challenges associated with joint auditing and reducing the expectations gap in auditing. The study recommended the necessity of the Sudanese Board of Accountants and Auditing to adopt joint auditing in the local environment by enacting legislation, laws and regulations to ensure the independence of auditors, and the need to work on activating international and regional partnerships on joint auditing to improve external audit work to reduce the expectations gap in auditing.